(3fRgI GdXQaGA hJMaI GdNdaGAs - (3YHGS Hf Ydj Hf OGhO Hf GdeXaQ jhSa GdQShdj GdZSGfj, Gdedc GdCaVd , J (B778 (3g` s ((3SdjeGf Hf MSjf Hf LGfe s)
(3ChdgG (B:s
(3agPG eNJUQ jTJed Ydi QShe GdNdaGA hBOGH NOeJge hGdJMjI hGdSdGe Ydjge hJbHjd GdCQV Hjf CjOge hZjQ Pdc ef BOGH eLGdSJge hBOGHge ai CfaSge hHjGf eG jLH Ydjge hbO LYdfG GdcJGH Ydi KdGKI CbSGe s
(3BNQgG (B:s
(3heYQaI cd TF NjQ ef Lgdg bd gh jSJhi GdPjf jYdehf hGdPjf dGjYdehf EfeG jJPcQ ChdhG GdCdHGH , hgPG BNQ eG YfjfG Hg ef LeY gPG GdeNJUQ Ydi MSH GdEecGf hESYGa GdReGf hGddg JYGdi fSCdg GdEYGfg hGdJhajb hGdZaQGf Efg cQje efGf QMef QMje s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B639s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdSjGSI hGdGLJeGYs